Simulation of Systems-of-Systems Dynamic Architectures - Manzano, Wallace; Graciano Neto, Valdemar Vicente; Nakagawa, Elisa Yumi (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e PráticaDO - 10.5753/cbsoft_estendido.2020.14632, 2020)
Systems-of-Systems (SoS) combine heterogeneous, independent systems to offer complex functionalities for highly dynamic smart applications. Due to their critical nature, SoS should be reliable and work without interruption since a failure could cause serious losses. SoS architectural design can facilitate the prediction of the impact of failures due to SoS behavior. However, existing approaches do not support such evaluation. The main contribution of this paper is to present Dynamic-SoS, an approach to predict, at design time, the SoS architectural behavior at runtime to evaluate whether the SoS can sustain their operation. Results of our multiple case studies reveal Dynamic-SoS is a promising approach that could contribute to the quality of SoS by reliably enabling prior assessment of their dynamic architecture.